2016
DOI: 10.5759/jscas.17.333
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of a camera operation for endoscopic sinus surgery using a navigation information

Abstract: Endoscopic sinus surgery(ESS)has been performed with a navigation system to reduce a risk of causing injuries and complications during the surgery. However, supporting the improvement of surgeonsskill levels is important to further improve the safety of ESS. We previously developed a method for analyzing and evaluating the motion of the forceps during a glioma surgery and a laparoscopic cholecystectomy in order to help surgeons to learn surgical skills. As a surgeon need to operate an endoscopic camera and a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…As in our previous study 15) , the calculation result showed that expert surgeons tended to manipulate the endoscope more efficiently, capturing the affected area from various viewpoints. Since it may be important to reduce the motion of the tip of an endoscope while obtaining wide views in the narrow nasal cavity in order to achieve safe surgery, these calculation results likely reflect important features of endoscope manipulation.…”
Section: .Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…As in our previous study 15) , the calculation result showed that expert surgeons tended to manipulate the endoscope more efficiently, capturing the affected area from various viewpoints. Since it may be important to reduce the motion of the tip of an endoscope while obtaining wide views in the narrow nasal cavity in order to achieve safe surgery, these calculation results likely reflect important features of endoscope manipulation.…”
Section: .Discussionmentioning
confidence: 61%
“…In particular, in the case of ESS, in which a surgeon performs the procedure as solo . In a previous study 15) , we developed and validated a navigation procedures during all the stages in this study.…”
Section: )−15)mentioning
confidence: 99%
See 3 more Smart Citations